Cell-Penetrating Antibodies For Targeting HIV-1 P24 Capsid Protein - Teow, Sin Yeang (2015)
The capsid protein plays seminal roles in both early and late stages of the HIV replication cycle. Hence, HIV-1 capsid protein is considered an important target for developing novel drugs to treat HIV/AIDS. Capsid molecule (CA)-targeting peptide inhibitors (CAP-1, CAI and NYAD-1) have been reported to disrupt the capsid protein functions in HIV-infected cells. However, the peptides are less stable in the blood, thus resulting in rapid clearance from the system and they can exhibit off-target activities. Monoclonal antibodies (MAbs) on the other hand, are stable and highly specific molecule,